Matching global cobalt demand under different scenarios for co-production and mining attractiveness - Alexandre Tisserant; Stefan Pauliuk (Journal of Economic Structures, 2016)
Many new and efficient technologies require "critical metals" to function. These metals are often extracted as by-product of another metal, and their future supply is therefore dependent on mining developments of the host metal. Supply of critical metals can also be constrained because of political instability, discouraging mining policies, or trade restrictions. Scenario analyses of future metal supply that take these factors into account would provide policy makers with information about possible supply shortages. We provide a scenario analysis for demand and supply of cobalt, a potentially critical metal mainly used not only in high performance alloys but also in lithium-ion batteries and catalysts. Cobalt is mainly extracted as by-product of copper and nickel. A multiregional input-output (MRIO) model for 20 world regions and 163 commodities was built from the EXIOBASE v2.2.0 multiregional supply and use table with the commodity technology construct. This MRIO model was hybridized by disaggregating cobalt flows from the nonferrous metal sector. Future cobalt demand in different world regions from 2007 to 2050 was then estimated, assuming region- and sector-specific GDP growth, constant technology, and constant background import shares. A dynamic stock model of regional reserves for seven different types of copper, cobalt, and nickel resources, augmented with optimization-based region-specific mining capacity estimates, was used to determine future cobalt supply. The investment attractiveness index developed by the Fraser Institute specifically for mining industry entered the optimization routine as a measure of the regional attractiveness of mining. The baseline scenario shows no cobalt supply constraints over the considered time period 2007-2050, and recovering about 60 % of cobalt content of the copper and nickel ore flows would be sufficient to match global cobalt demand. When simulating a hypothetical sudden supply dropout in Africa during the period 2020-2035, we found that shortages in cobalt supply might occur in such scenarios.
Keywords: 330; Cobalt; Copper; Nickel; Scenario analysis; Critical metals; Dynamic input-output analysis; Hybrid multiregional input-output model; Companion metals; By-product